An in-vitro evaluation of antibacterial activity of curcumin against common endodontic bacteria - Praveenkumar S. Mandroli and Kishor Bhat (Journal of Applied Pharmaceutical Science, 2013)
Aim of the study was to investigate the anti-bacterial potential of curcumin, against standard strains of common endodontic bacteria. The bacterial strains of Streptococcus mutans (ATCC 35668), Actinomyces viscosus (ATCC 10048), Lactobacillus casei (ATCC 334), Porphyromonas gingivalis (ATCC 33277), Prevotella intermedia (ATCC 25611), Enterococcus faecalis (ATCC 29212) from the stock were revived by plating on blood agar medium. Isolated colonies were transferred to sterile Brain Heart Infusion (BHI) broth and once again incubated overnight. The growth concentration was adjusted to 5 X 105 organisms / ml by using 0.5 McFarland’s turbidity standard. MIC was determined, by serial broth dilution of curcumin to 500, 250,125, 62.5, 31.25, 16, 8, 4, 2, 1 μg /ml. respectively. The tubes were then incubated for 24 hours at 37o C. The last tube with clear supernatant was considered to be without any growth and taken as MIC value. Mean MIC values of curcumin were as follows: S. mutans (333.33 μg /ml), A. viscosus (167.67 μg /ml), L. casei (125 μg /ml), P. gingivalis (125 μg /ml), and P. intermedia (208.33 μg /ml). There was no action against E. faecalis. Thus, we can conclude that curcumin has the potential to be developed into medicament for the treatment of various endodontic diseases.
Keywords: Anti-bacterial, Anti-inflammatory Curcumin, Minimum inhibitory concentration.